Where Truth Happens: The Nepali House as Mandala: Part 4: The Human in Culture - Gray, John (Anthropologica, 2022)
This article documents the existential possibility of the philosophical unreality of fundamental unity and diversity in the world. I explore this human experience through the cosmology and domestic architecture of Hindus in Nepal. In tantric Hinduism of Nepal, the presence of the worldly diversity of people and things as expressions of a cosmological unity is an existential experience and a fundamental moral issue. I describe how domestic space, configured in everyday activities as a mandala, is the medium through which these abstract cosmological ideas are given tangible form. Domestic mandalas are maps, microcosms and revelations of the truth of the cosmos. In them, everyday life becomes a dialectic of the practical and cosmological directed toward an ever-deepening tacit and embodied revelation of the ultimate unity and truth of the universe.